PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING DENGAN TEKNIK PROBING PROMPTING DALAM PEMBELAJARAN MATEMATIKA MATERI BARISAN DAN DERET ARITMATIKA - Sulangi, Victor R; Mangobi, James U. L.; Siby, Rishadewi (Universitas Negeri Manado, 2020)
Â ABSTRACT. This research was determined whether the student learning outcomes used the Problem Posing learning model with Probing Prompting techniques on the sequence and series arithmetic leson more than the KKM set by SMK Negeri 1 Kakas whisch is 70. The research was categorized as quasi experimental research. The subjects in this research were students of class X in the TKJ Department. The results of data analysis, obtained an average of the student learning outcomes in the experimental class used the Probing Posing model with Probing Prompting technique was 79.9, with a maximum score of 90 and a minimum score of 66. So can be conclude that the average learning outcomes of the students who used the Probing Posing model with Probing Prompting techniques on the Â sequence and series arithmetic leson more than the KKM set by the SMK Negeri 1 Kakas school which is 70.Â Key Words: Problem Posing, Probing Prompting, The Sequence and Series Arithmetic